2002
DOI: 10.1007/s003390201638
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced partial order in the spin ice dysprosium titanate

Abstract: Neutron scattering has been used to investigate the magnetic correlations in the the spin ice material dysprosium titanate, Dy 2 Ti 2 O 7 . An isotopically enriched sample was used to minimise neutron absorption. In zero field no magnetic order was observed down to 50 mK but the magnetic diffuse scattering was in qualitative agreement with that expected for the disordered low temperature state of dipolar spin ice. Application of a field of ≈ 0.8T in the [100] direction led to long range order. With the field a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…[57,107,122] and the bulk measurements of Ref. [120] are in reasonable agreement regarding the general features of the phase diagram shown in Figure 7.28.…”
Section: [110] Directionsupporting
confidence: 75%
“…[57,107,122] and the bulk measurements of Ref. [120] are in reasonable agreement regarding the general features of the phase diagram shown in Figure 7.28.…”
Section: [110] Directionsupporting
confidence: 75%
“…Recently, it has been observed that the cubic pyrochlore Dy 2 Ti 2 O 7 demonstrates the spin ice state and the coexistence of long range ferromagnetic and short range antiferromagnetic order in a magnetic field applied along the [1 1 0] axis [1,2]. For the information on phonons, charge carriers and spins, this geometrically frustrated pyrochlore Dy 2 Ti 2 O 7 (space group O h 7 ) had been studied experimentally for its infrared and Raman modes [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent experiments 60,61,62,64,80 have shown a rich variety of new behavior when spin ice materials are subjected to such a field, which warrants some theoretical investigation.…”
Section: Dipolar Spin Ice In Magnetic Fieldmentioning
confidence: 99%
“…They suggested that this behavior would arise from long-range ferromagnetic order occurring in field-coupled spin chains (called α chains by Hiroi 62 ), and short-range "antiferromagnetic" order occurring in the field-decoupled spin chains (β chains). 80 In this argument, the true ground state is a q = X structure that is dynamically inhibited from being accessed on experimental timescales.…”
Section: 80mentioning
confidence: 99%
See 1 more Smart Citation